Strain, cell density, and nutrient condition affect patterns of diurnal vertical migration and superoxide production in a red-tide alga - Tomoyuki Shikata; Saho Kitatsuji; Koki Yuasa (Frontiers in Cell and Developmental Biology, 2023)
A red tide occurs when cell densities of autotrophic microalgae and some heterotrophic protists increase dramatically and thereby change the color of the sea. Red tides sometimes have negative impacts on human activities, such as fisheries and tourism. Most red-tide flagellates display diurnal vertical migration (DVM) in which cells normally migrate upward during the day and downward at night. This behavior promotes active growth, due to the effective acquisition of nutrients and light, as well as population density increase and cell aggregation. However, the factors and their interactions influencing DVM remain to be clarified, such that no algorithm exists that can precisely simulate the DVM pattern and the development of a red tide in the field. Chattonella marina complex (hereafter Chattonella) is a representative microalga of harmful red tides and some previous studies has suggested that Chattonella’s DVM plays important roles in development of a red tide. Chattonella can produce a large amount of superoxide (•O2−), which is responsible for the regulation of various physiological processes as well as its toxicity against microorganisms and animals. In the present study, we examined the effects of strain, growth phase, cell density, and nutrient deficiency on the pattern of DVM. In addition, we also measured the •O2− level in most experiments to assess the relationship between DVM and •O2− production. Some strains displayed clear DVM, whereas others aggregated at the surface all day in a fixed condition. Strains’ DVM patterns did not show a relationship with •O2− production. Moreover, the DVM became less clear at high cell density and in nitrogen- or phosphorus-depleted conditions. Although a previous study reported that the •O2− production rate increased during the light period and decreased during the dark period, regardless of cell density, the diurnal pattern of •O2− became less clear at a higher cell density in a Chattonella strain used in the present study. Our findings indicate that DVM and •O2− production by a Chattonella population composed of various strains can change across developmental phases and environmental conditions. This characteristic may produce adaptability in species and increase the chances of a massive population increase.